A STUDY OF THE UNDERGROWTH VEGETATION OF SEMPU ISLAND, EAST JAVA, INDONESIA - ASEP SADILI; KUSWATA KARTAWINATA (REINWARDTIA, 2016)
SADILI, A. & KARTAWINATA, K. 2016. A study of the undergrowth vegetation of Sempu Island, East Java, Indonesia. Reinwardtia 15(1): 1 - 9. — A study of forest floor vegetation in coastal forest (site 1) and inland lowland forest (site 2) was carried out at the Sempu Island Nature Reserve, Malang Regency, East Java. The objective of the study is to obtain data on plant species diversity, species composition and structure of the forest floor vegetation. In each site the vegetation was sampled with a plot of 1 m × 50 m, which was divided into 50 subplots of 1 m × 1 m each. Overall from the two plots we recorded 59 species, 57 genera and 39 families. Shannon-Wienner diversity indices (H’) were relatively high. i.e., 4.47 in Plot 1 and 3.2 in Plot 2, with a mean of 3.84. The number of the seedlings of shrubs and trees was greater than that of the herbaceous species. The families having the highest number of species were Euphorbiaceae (6 species) and Fabaceae (5 species). Based on dominant species the vegetation in Plot 1 was designated as Scleria lithosperma-Asystasia nemorum community type, while in Plot 2 Pterospermum javanicum-Knema sp. community type. The similarity index between these community types was only 18%. Only P. javanicum  showed a good regeneration and the regeneration of other species in the two community types was poor, indicating unclear floristic changes in the forest of the Sempu Island.